الكفاءة الذاتية المدركة لدى طلبة الدراسات العليا - صالح, زينة علي; حسن, فؤاد كاظم (Tasnim International Journal for Human, Social and Legal Sciences, 2025)
The. currently research aims to trifae: 1. Perceived self-efficacy amidst graduate students. The research sample was determined from (400) male and female postgraduate students)Masters – PhD ((males - females) at Al-Qadisiyah University, who University؛ They were selected us with a proportinal approach. Regarding the research tool, the researcher built a tool to measure the variable of perceived self-efficacy based on the theory of) Bandura: 1997) The scale consisted of) 36) paragraphs after extracting the psychometric properties؛ a researcher adopted the descriptive approach. The researcher concluded that the research sample enjoys perceived self-efficacy. Based on what the research results showed, the researchers, presented, a seti of recommendationss and suggestion's.